A review of nanomaterials from synthetic and natural molecules for prospective breast cancer nanotherapy - Kumar, Pankaj; Mangla, Bharti; Javed, Shamama; Ahsan, Waquar; Musyuni, Pankaj; Sivadasan, Durgaramani; Alqahtani, Saad S.; Aggarwal, Geeta (Frontiers in Pharmacology, 2023)
Breast cancer being one of the most frequent cancers in women accounts for almost a quarter of all cancer cases. Early and late-stage breast cancer outcomes have improved dramatically, with considerable gains in overall survival rate and disease-free state. However, the current therapy of breast cancer suffers from drug resistance leading to relapse and recurrence of the disease. Also, the currently used synthetic and natural agents have bioavailability issues which limit their use. Recently, nanocarriers-assisted delivery of synthetic and natural anticancer drugs has been introduced to the breast cancer therapy which alienates the limitations associated with the current therapy to a great extent. Significant progress has lately been made in the realm of nanotechnology, which proved to be vital in the fight against drug resistance. Nanotechnology has been successfully applied in the effective and improved therapy of different forms of breast cancer including invasive, non-invasive as well as triple negative breast cancer (TNBC), etc. This review presents a comprehensive overview of various nanoformulations prepared for the improved delivery of synthetic and natural anticancer drugs alone or in combination showing better efficacy and pharmacokinetics. In addition to this, various ongoing and completed clinical studies and patents granted on nanotechnology-based breast cancer drug delivery are also reviewed.